PENGARUH BEBAN KERJA, EMPLOYEE ENGAGEMENT DAN LINGKUNGAN KERJA TERHADAP WORK-LIFE BALANCE PADA MAHASISWA YANG BEKERJA DI STIE INDONESIA JAKARTA - Nurlela, Nurlela; Pragiwani, Meita (Jurnal Ekonomi Manajemen Bisnis Dan Akuntansi : EMBA, 2025)
Abstract- This study aims to determine the effect of workload, employee engagement and work environment on work life balance. This study was conducted on students at STIE Indonesia Jakarta in employee classes or students who work. The number of samples was 146. This research method uses a survey method, by distributing questionnaires to respondents, the type of data used is quantitative data, the data source used is primary data, the data obtained is processed using the SEM PLS 4.0 method. The results of the study indicate that there is a positive effect of workload on work life balance and there is a positive effect of employee engagement on work life balance, and there is no effect of the work environment on work life balance